Total Knee Replacement of Synovial Haemangioma of The Knee Joint in a 44-Year-Old Male: A Case Report - Idulhaq, Mujaddid; Saputra, Rhyan Darma; Wasita, Brian; Sabariyah, Lely; Gardjito, Fajar Baskoro; Nursulistyo, Fajar (Indonesian Journal of Cancer, 2024)
Introduction: Synovial hemangioma is a rare illness frequently misdiagnosed, leading to years of inaction. In this study, we aim to discover the consequences of untreated hemangioma of the knee joint. Case Presentation: Our patient was a 44-year-old male who experienced recurring pain in his left knee. The previous year, the patient experienced pain in his left knee while walking, which has subsided with rest. Although he has been performing radiography at multiple hospitals since 2019, no problems have been recorded. We detected a mass after performing magnetic resonance imaging. The T1-weighted sequence + contras near the medial femoral condyle revealed a homogeneous mass with high intensity. We decided to conduct surgical intervention and total knee replacement. Postsurgical, the patient regained symptom-free. Conclusions: Because of the limited radiographic capacity, synovial hemangioma is uncommon and challenging to diagnose on an outpatient basis. Magnetic resonance imaging and angiography are highly beneficial. If intraarticular hemangiomas are not considered, they can cause bony dysplasia and multiple clinical manifestations. Initial total excision can be conducted to decrease the chance of hemarthrosis.